2016
DOI: 10.1093/jos/ffw010
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Alternatives in the Acquisition of Simple and Complex Disjunctions in French and Japanese

Abstract: When interpreting disjunctive sentences of the form 'A or B,' young children have been reported to differ from adults in two ways. First, children have been reported to interpret disjunction inclusively rather than exclusively, accepting 'A or B' in contexts in which both A and B are true (Gualmini, Crain, Meroni, Chierchia & Guasti 2001; Chierchia, Crain, Guasti & Thornton 2001). Second, some children have been reported to interpret disjunction conjunctively, rejecting 'A or B' in contexts in which only one o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(54 citation statements)
references
References 34 publications
5
46
0
3
Order By: Relevance
“…Children's troubles with scalar implicatures are not confined solely to quantifiers, however. Developmental work on logical connectives indicates that children also have difficulties computing a scalar implicature with “or” to generate a disjunctive rather than conjunctive interpretation (Singh et al., ; Tieu et al., ; Zhou, Romoli, & Crain, ). Interpreting a statement such as “The girl has a balloon or a ball” as disjunctive requires the listener to draw a scalar implicature that the girl has either a balloon or a ball but does not have both (Singh et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children's troubles with scalar implicatures are not confined solely to quantifiers, however. Developmental work on logical connectives indicates that children also have difficulties computing a scalar implicature with “or” to generate a disjunctive rather than conjunctive interpretation (Singh et al., ; Tieu et al., ; Zhou, Romoli, & Crain, ). Interpreting a statement such as “The girl has a balloon or a ball” as disjunctive requires the listener to draw a scalar implicature that the girl has either a balloon or a ball but does not have both (Singh et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Interpreting a statement such as “The girl has a balloon or a ball” as disjunctive requires the listener to draw a scalar implicature that the girl has either a balloon or a ball but does not have both (Singh et al., ). Children favor inclusive over adult‐like exclusive readings of or in these tasks, not because they don't understand the semantics of “or” in this task, or are unable to compute implicatures, but because they cannot use the full set of alternatives to draw the implicature (Singh et al., ; Tieu et al., ; Zhou et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tieu et al observed that children computed free choice inferences around 90% of the time, whereas they computed standard implicatures involving plain disjunction ("or"/"and") and modals ("may"/"must") at typically low rates. In addition to free choice inferences, children have been reported to compute a handful of other inferences at adult-like rates, including the exactly-n inference of numerals (Papafragou & Musolino 2003;Barner & Bachrach 2010), ad hoc implicatures (Barner et al 2011;Stiller et al 2015), ignorance inferences (Hochstein et al 2016), and various inferences of simple and embedded disjunctions (Singh et al 2016;Tieu et al 2017). The apparent variability in children's performance on implicatures (i.e.…”
Section: B ⇝ Jack Can Have Cake and Jack Can Have Ice Creammentioning
confidence: 99%
“…Others [11] were concerned with the positive polarity in Japanese. Still others [17] focused on simple and complex disjunctions in French and Japanese, children's interpretation of disjunction in the scope of 'before' [17] and other issues. The authors generally agree that this kind of question is rather difficult and its fullfledged acquisition is completed rather late in the language development.…”
mentioning
confidence: 99%